INFLUENCE OF ACCELERATED AGEING ON PULL-OFF STRENGTH OF CONCRETE PRODUCED WITH RECYCLED CONCRETE AGGREGATE AND BLENDED WITH HEMP FIBERS - Šupić, Slobodan; Poletanović, Bojan; Radonjanin, Vlastimir; Malešev, Mirjana; Merta, Ildiko; Pantić, Vladan (Journal of Applied Engineering Science, 2024)
As a result of rising demand for non-renewable resources, high energy consumption, and, most importantly, unfavourable environmental consequences, the construction sector is switching to environmentally friendly products. Some feasible options for developing alternative low-cost, renewable and green materials include the utilization of natural fibers and recycled materials from construction and demolition (C&D) waste. This report summarizes a portion of the experimental research being conducted as part of a bilateral research project: ''BIO-based cementitious composites with recycled aggregates (Bio-gates),'' performed by teams from Novi Sad's Faculty of Technical Sciences and Vienna's Technical University. This research explores the impact of hemp fibers and recycled concrete aggregate (RCA) on the pull off strength of concrete, cured under normal conditions and subjected to wet/dry cycles (accelerated ageing regime). The obtained results revealed that RCA has no detrimental effect on the adhesive bond, while hemp fibers reduce the pull off strength of concrete to a greater extent. Nonetheless, adhesion to the substrate may be regarded satisfactory for all tested concrete types when the limit values specified in the applicable regulations are taken into account.
Keywords: environmentally friendly products, recycled concrete aggregate, hemp fibers, pull off strength